THE ROLE OF COMMUNITY-BASED RESOURCES IN FORMING A NEW MICROBUSINESS - Andriany, Lussia Mariesti (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2024)
This study aims to analyze the role of community-based resources in the formation of a new organization. This is conceptualized as resources that are socially and culturally constructed within a community, can be mobilized easily and interpreted independently depending on the purpose of business owners. It is argued that community-based resources play a critical role in forming a new organization. We employ a qualitative approach to explain its role in establishing a new microbusiness in Indonesia. Based on the interview, we found that community-based resources that are represented by new ingredients and cooking methods (i.e., a new way of producing food) played significant roles in new micro-businesses’ emergence in terms of expanding customers’ demand, providing a clear timing for new organizational emergence, and allowing the condition of resource-driven structuration.